2010
DOI: 10.4049/jimmunol.0902857
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Property of Antibodies against N-Glycolylneuraminic Acid Epitopes in Cytidine Monophospho–N-Acetylneuraminic Acid Hydroxylase-Deficient Mice

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 46 publications
0
50
0
Order By: Relevance
“…Humans, but not nonhuman primates, also make a complex array of antibody to a common mammalian sialic acid modification Neu5GC . This antibody reactivity is widely expected to contribute to xenograft rejection in humans but its significance remains uncertain due to the absence of anti‐Neu5GC antibody in experimental non‐human primate models. Screening strategies based on panels of defined oligosaccharides have failed to detect xenogeneic sensitization to other common oligosaccharides (Forssman antigen and α‐ and β‐lactosamine) .…”
Section: Discussionmentioning
confidence: 99%
“…Humans, but not nonhuman primates, also make a complex array of antibody to a common mammalian sialic acid modification Neu5GC . This antibody reactivity is widely expected to contribute to xenograft rejection in humans but its significance remains uncertain due to the absence of anti‐Neu5GC antibody in experimental non‐human primate models. Screening strategies based on panels of defined oligosaccharides have failed to detect xenogeneic sensitization to other common oligosaccharides (Forssman antigen and α‐ and β‐lactosamine) .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition is overcome however with a larger dose of islets and isogenic CMAH +/+ hearts are not rejected by CMAH −/− recipients. (40) Under similar conditions GalT-KO mice reject isogenic GalT + mouse hearts (41) suggesting that the pathogenicity of anti-Neu5Gc antibody may be less then anti-Gal antibody.…”
Section: Human Non-gal Antibodiesmentioning
confidence: 99%
“…To mimic the human situation, we used mice with a human-like defect in the Cmah gene, which encodes the enzyme that generates activated Neu5Gc (CMP-Neu5Gc) 18 . Such mice can make anti-Neu5Gc antibodies upon immunization with glycosidically-bound but not free Neu5Gc 19,20 . However, these previous studies used whole rodent or chimpanzee cells for immunization, an obviously artificial approach.…”
mentioning
confidence: 99%
“…In this regard, we have also suggested that Neu5Gc contamination of stem cells and other cell types intended for human therapy could pose risks 32,33 . Also, others have recently reported that Cmah null mice can reject Neu5Gc-positive wild-type organ transplants via complement-fixing anti-Neu5Gc antibodies 20 .…”
mentioning
confidence: 99%